Comparison of Safety between Subclavian and Internal Jugular Central Venous Catheterization in patients admitted to the Medical ICU. A Randomized Controlled Trial - Ambreen Asif, Sabira Sharif, Kashif Aziz Ahmad, Samrah Fatima, Sohaib Akbar, Rabea Rashed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Central venous catheterization (CVC) is a critical procedure in intensive care, most commonly performed via the subclavian or internal jugular veins. Each route has distinct advantages and complication risks, making site selection clinically important. Objectives: To compare the safety profile, complication rates, and procedural outcomes of subclavian versus internal jugular CVC insertion in critically ill adults using real-time ultrasound guidance. Methods: This randomized controlled trial was conducted in the Medical Unit 3, Lahore General Hospital, Lahore, Pakistan, from March 2022 to May 2023. A total of 100 adult patients requiring CVC for >48 hours were randomly assigned to the subclavian group (n = 50) or internal jugular group (n = 50). All insertions were performed under aseptic precautions and real-time ultrasound guidance. Primary outcomes were mechanical complications (pneumothorax, hemothorax, arterial puncture, malposition) and catheter-related bloodstream infections (CRBSIs). Secondary outcomes included insertion attempts, procedure time, and catheter malfunction. Data were analyzed using SPSS v26, with p < 0.05 considered significant. Results: Baseline demographics and illness severity were similar in both groups. Pneumothorax occurred in 3 patients (6.0%) in the subclavian group versus none in the internal jugular group (p = 0.04). CRBSIs were significantly lower in the subclavian group (2 cases, 4.0%) compared to the internal jugular group (7 cases, 14.0%) (p = 0.03). Other complications, including arterial puncture (4.0% vs. 6.0%) and malposition (2.0% vs. 4.0%), were infrequent and comparable. First-attempt success rates were high in both groups (82.0% vs. 80.0%). Conclusion: Both sites are safe with ultrasound guidance. The subclavian approach offers lower infection rates but a higher risk of pneumothorax, while the internal jugular site avoids pneumothorax but has increased infection risk. Keywords: Central venous catheterization, subclavian vein, internal jugular vein, complications, ultrasound guidance.